Patent Foramen Ovale Closure in Obstructive Sleep Apnea Improves Blood Pressure and Cardiovascular Function. Issue 5 (November 2015) - Rimoldi, Stefano F.; Ott, Sebastian; Rexhaj, Emrush; de Marchi, Stefano F.; Allemann, Yves; Gugger, Matthias; Scherrer, Urs; Seiler, Christian
<x xml:space="preserve">Abstract</x> Obstructive sleep apnea (OSA) is a frequent syndrome characterized by intermittent hypoxemia and increased prevalence of arterial hypertension and cardiovascular morbidity. In OSA, the presence of patent foramen ovale (PFO) is associated with increased number of apneas and more severe oxygen desaturation. We hypothesized that PFO closure improves sleep-disordered breathing and, in turn, has favorable effects on vascular function and arterial blood pressure. In 40 consecutive patients with newly diagnosed OSA, we searched for PFO. After initial cardiovascular assessment, the 14 patients with PFO underwent initial device closure and the 26 without PFO served as control group. Conventional treatment for OSA was postponed for 3 months in both groups, and polysomnographic and cardiovascular examinations were repeated at the end of the follow-up period. PFO closure significantly improved the apnea–hypopnea index (ΔAHI −7.9±10.4 versus +4.7±13.1 events/h, P=0.0009, PFO closure versus control), the oxygen desaturation index (ΔODI −7.6±16.6 versus +7.6±17.0 events/h, P=0.01), and the number of patients with severe OSA decreased significantly after PFO closure (79% versus 21%, P=0.007). The following cardiovascular parameters improved significantly in the PFO closure group, although remained unchanged in controls: brachial artery flow–mediated vasodilation, carotid artery stiffness, nocturnal systolic and diastolic blood pressure (−7 mm Hg, P=0.009 and −3 mm Hg, P=0.04, respectively), blood pressure dipping, and left ventricular diastolic function. In conclusion, PFO closure in OSA patients improves sleep-disordered breathing and nocturnal oxygenation. This translates into an improvement of endothelial function and vascular stiffening, a decrease of nighttime blood pressure, restoration of the dipping pattern, and improvement of left ventricular diastolic function. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01780207.